An Analysis of Early Reading Ability of Class 1 in Elementary School: Analisis Kemampuan Membaca Permulaan Kelas 1 Sekolah Dasar - Janawati , Desak Putu Anom; Sulantara, I Made Eka (Universitas Muhammadiyah Sidoarjo, 2021)
This study aimed at describing students’ ability of early reading in SD Negeri 3 Ubud. This is a qualitative descriptive research. The samples were all of class I in total of 22 students comprising of 11 males and 11 females. The data were collected by using observation sheet and test of early reading ability. The data were analyzed by using Likert scale. The research finding showed that students’ ability of early reading of class I in SD Negeri 3 Ubud was categorized as good (B) with 85% percentage.